Pilot randomized trial of a volitional help sheet‐based tool to increase leisure time physical activity in breast cancer survivors. Issue 3 (16th May 2018) - Chapman, Janine; Fletcher, Chloe; Flight, Ingrid; Wilson, Carlene
Abstract : Objectives: To develop and test a volitional help sheet‐based tool to improve physical activity in breast cancer survivors compared to a standard self‐generated implementation intention intervention. Design: Pilot randomized trial conducted online over 3 months. Methods: Participants were randomized to an online volitional help sheet ( n = 50) or implementation intention ( n = 51) intervention. Measures were taken at baseline, 1 and 3 months. The main outcome measure was moderate‐strenuous leisure time physical activity. Secondary outcomes were health‐related quality of life and mood. Results: Participants exposed to the volitional help sheet and implementation intention interventions showed similar effects after 1 month, with both groups reporting a significant increase in moderate‐strenuous physical activity. After 3 months, the initial increase in physical activity was maintained by the volitional help sheet group, but not the implementation intention group. Improvements were also found for negative affect and emotional quality of life. Conclusion: While both interventions show promise in promoting physical activity in breast cancer survivors, the volitional help sheet may be more effective for facilitating lasting change and emotional well‐being. Findings suggest that the volitional help sheet may have potential to offer a cost‐effective contribution to consumer‐led tertiary preventive health. Future research should test these initial findings in a definitive trial. Statement of contribution What is already known on this subject? Physical activity is important for optimizing health in breast cancer survivors. Despite this, physical activity in this cohort remains low. Theory‐based strategies are needed to help breast cancer survivors independently manage and maintain regular physical activity over the long term. What does this study add? Online planning interventions can improve physical activity in breast cancer survivors. Volitional help sheets, but not implementation intentions, show sustained effects for 3 months. The intervention shows promise as a potential low‐cost addition to long‐term survivorship care plans.